GRAMMATICAL PROBLEMS OF TRANSLATION - Jumaboyeva Madina Abdumannob qizi; Egamberdiyeva Iroda; Egamberdiyev Jasurbek (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Grammatical problems of translation refer to the difficulties that arise when translating between two languages that have different grammatical structures. This paper explain clearly to this topic.